Gastrokine 1 mRNA in human sera is not informative biomarker for gastric cancer. Issue 1 (December 2016) - Villano, Valentina; Di Stadio, Chiara; Federico, Antonella; Altieri, Filomena; Miselli, Giuseppina; De Palma, Maurizio; Rippa, Emilia; Arcari, Paolo
Abstract Background We aimed to ascertain if Gastrokine 1 mRNA in the sera of patients with gastric cancer might be an informative biomarker for the disease. Results Analysis of GKN1 mRNA in serum samples from healthy individuals (n  = 23) and from patients with diagnosis of gastric cancer (n  = 16), performed by using absolute quantification based on standard curve method, did not show any significative statistical difference between the two unpaired group of individuals. Conclusions Our preliminary results did not confirm GKN1 as a potential biomarker for gastric cancer.